Indigenous girls and the violence of settler colonial policing - Dhillon, Jaskiran K. (Decolonization: Indigeneity, Education & Society, 2015)
In cities and towns across Canada, Indigenous girls are being hunted, harassed, and criminalized by local law enforcement agents and the Royal Canadian Mounted Police. These normalized outbreaks of state control, often punctuated by the use of deadly force, are not isolated incidents in an otherwise just and fair social order. Rather, they are reflective of Indigenous girls’ daily realities embedded within the structure of an ongoing settler colonial social context that has strategically invented the criminal justice system to secure and maintain settler sovereignty. As such, this paper aims to redirect our critical analysis of the policing and caging of Indigenous girls through the geopolitics of settler colonialism. In the wake of mass protests against colonial state violence throughout 2014, resistance decrying the justice system and insisting that #BlackLivesMatters and that Indigenous lives matter, I argue that we have an urgent need to listen to the stories that Indigenous girls have to tell. These are not just any stories, but narratives that profoundly destabilize the hubristic portrayal of Canada as a humanitarian nation cleansed of settler colonial rule.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; femmes* et filles autochtones disparues et assassinées; féminisme décolonial; histoire et politique; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violences; violences d'état

Actualité de l’intersectionnalité dans la recherche féministe au Québec et dans la francophonie canadienne - Bourque, Dominique; Maillé, Chantal (Recherches féministes, 2015)
Introduction du numéro "Intersectionnalité" de la revue Recherches féministes, nov 2015.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; har4600; histoire et politique; intersectionnalité; premier cycle; québec; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études féministes; études littéraires

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

Nānīawig Māmawe Nīnawind. Debout et solidaires. Femmes autochtones disparues ou assassinées au Québec - Québec, Femmes autochtones au; Bergeron, Annie; Boileau, Alana; Lévesque, Carole (Femmes autotchtones au Québec, 2015)
Le présent document fait état des résultats d’une enquête exploratoire effectuée par Femmes Autochtones au Québec (FAQ) en ce qui a trait à la situation des femmes autochtones disparues ou assassinées au Québec. Cette enquête a bénéficié du soutien financier du ministère de la Justice du Québec et du Réseau de recherche et de connaissances relatives aux peuples autochtones (DIALOG). Elle visait principalement à consigner et à mettre en valeur la parole des Autochtones de différents horizons et provenances, de même que celles des membres des familles de femmes autochtones disparues ou assassinées, principales personnes concernées par la problématique.
Keywords: amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; justice sociale; pol4105; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences